2023
DOI: 10.1177/15248380231171186
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Empirical Studies Measuring Training Effects on Biases Evidenced by Professionals toward Intimate Partner Violence

Abstract: A professional’s response to a client’s disclosure of intimate partner violence (IPV) is shown to significantly impact client outcomes. The quality of a professional’s response is largely influenced by that professional’s beliefs or biases surrounding IPV. This systematic review examined empirical studies conducted in North America and published between 2000 and 2020 evaluating training effects on biases held by professional groups toward victim-survivors of IPV. Search and extraction were conducted in accorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(239 reference statements)
1
1
0
Order By: Relevance
“…Similar results were found with the relationship between perceived stress and feelings of institutional betrayal, with those experiencing higher stress levels because of the pandemic feeling more betrayed by their institution. These results build on prior research noting that as first responders experienced increased stressors throughout the pandemic, they repeatedly felt unsupported or not "cared for" by their institution (Hendrickson et al, 2022;Sereno et al, 2023). Our findings also showed that as perceived stress levels increased, so did both maladaptive and adaptive coping frequencies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were found with the relationship between perceived stress and feelings of institutional betrayal, with those experiencing higher stress levels because of the pandemic feeling more betrayed by their institution. These results build on prior research noting that as first responders experienced increased stressors throughout the pandemic, they repeatedly felt unsupported or not "cared for" by their institution (Hendrickson et al, 2022;Sereno et al, 2023). Our findings also showed that as perceived stress levels increased, so did both maladaptive and adaptive coping frequencies.…”
Section: Discussionsupporting
confidence: 85%
“…The current relationship between first responders and their community is also well-researched, with supportive responses related to the reinforcement of help-seeking behavior, enhanced feelings of capability and resilience, and an increased likelihood of leaving the abusive relationship. On the other hand, unsupportive responses may lead to secondary victimization and the suppression of help-seeking behavior (Sereno et al, 2023). This has become of particular importance given the increased rates of IPV during the pandemic (Wood, Yirgu, et al, 2022).…”
Section: Present Studymentioning
confidence: 99%